Wealth Management Models in India - Mody, Riddhi (2007)
High performance levels and accelerating economic indicators worldwide has led to an increase in the number of high net worth individuals (HNWIs) and the amount of wealth they hold in recent years. After the economic reforms of 1991, the Indian economy has opened up gradually and there has been an increase in the inflow of foreign funds. As a result, investors in India and worldwide are worried about managing their wealth and looking at alternative ways to maintaining and creating wealth. Wealth management is defined as taking care of the needs of the affluent clients, their families and their businesses as part of a long term, consultative relationship. It is best conceptualized as a platform where a number of different sets of services and products are provided. It is a full service model that offers advice on investment management, estate planning, retirement, tax, asset protection, and cash flow and debt protection. This study draws comparisons between the wealth management models of four Indian companies and develops a comprehensive model based on the above four models. This study proves that the wealth management models used today are a combination of the Modern Portfolio Theory (MPT) and behavioural finance theory, hence bringing about a shift from the traditional models to a customer centric and needs based approach.